Establishing Regional Regulations for the Protection of Local Wisdom - Yenny Febrianty; Joko Sriwidodo; Priyaldi Priyaldi (Universitas Lampung, 2023)
Local governments structure legislation into a policy rule regarding the protection of local wisdom that must be carried out due to globalization. Globalization is something that cannot be avoided. Its influence can become a problem or negatively impact fading cultural identity if the community wrongly addresses it. This is different if the community and local government can respond positively to globalization because this can increase the community's cultural identity. This paper focuses on the study of how local government policies maintain cultural traditions as a pearl of local wisdom? and what is the paradigm of the local government in establishing regional regulations regarding the protection of local wisdom. The approach method utilized is a socio-legal or socio-juridical approach. This research was carried out in the city of Pariaman, West Sumatra. The research data, both primary and secondary data, were analyzed qualitatively. Based on the research result, the concrete paradigm of the Regional Government in protecting the values of local wisdom is a regional legislation on safeguarding indigenous culture as a Pariaman community's local wisdom. It can be interpreted that the Regional Regulation is a concrete agreement towards the ideal concept of protecting local wisdom in the Pariaman community. The ideal concept seen from the substantive values of protecting Local wisdom's worth in the Pariaman community must be founded on sociological, philosophical, and legal considerations. These three factors prioritize or rank the values within this local wisdom.